RENEWABLE ENERGY STATUS AND HYDROPOWER IN SOME DEVELOPING COUNTRIES AND FOCUS ON TURKEY - Yuksel, Ibrahim; Arman, Hasan; Serencam, Ugur; Songur, Mehmet; Demirel, I. Halil (PARLAR SCIENTIFIC PUBLICATIONS (P S P), 2016)
The share of renewable energies varies quite a lot in the developing countries, both in terms of total primary energy and electricity generation. Several different policy instruments are in use for promoting renewable energies, such as quota obligations, price subsidies, and taxes/tax exemptions on energy. Some countries such as Turkey, also have specific political programs for renewable energies. The obstacles and success conditions mainly deal with geographical, economic, administrative and political factors. The Republic of Turkey forms a natural bridge between Europe and Asia and the country has a relatively young population in both Europe and Asia. Turkey aims to utilize its energy potential, including from renewable sources, in a cost-effective manner In its efforts to promote renewable energy, the government has focused on electricity, but has recently started to pay more attention to heat. On the other hand, Turkey's geographical location has several advantages for extensive use of most of the renewable energy sources. In this regard, renewable energy resources appear the most efficient and effective solutions for clean and sustainable energy development in Turkey. In addition to Turkey has a great hydropower, especially small hydropower potential. This paper deals with Turkey's renewable energy status in developing countries.
Keywords: Renewable energy; hydropower; developing counties; Turkey; HYDROELECTRIC POWER; Environmental Sciences & Ecology